2013
DOI: 10.1016/j.bbapap.2013.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and archaeal globins — A revised perspective

Abstract: A bioinformatics survey of putative globins in over 2200 bacterial and some 140 archaeal genomes revealed that over half the bacterial and approximately one fifth of archaeal genomes contain genes encoding globins that were classified into three families: the M (myoglobin-like), and S (sensor) families all exhibiting the canonical 3/3 myoglobin fold, and the T family (truncated myoglobin fold). Although the M family comprises 2 subfamilies, flavohemoglobins (FHbs) and single domain globins (SDgbs), the S famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 131 publications
(100 reference statements)
3
107
2
Order By: Relevance
“…The recent and rapid accumulation of genomic information has resulted in a substantial increase in newly recognized globins. Bioinformatic genome surveys revealed that more than 50% of the bacterial, approximately 20% of the archaeal and almost 90% of the eukaryote genomes contain genes encoding globins [1,[5][6][7]. Despite their great variety in function and amino acid sequence, most of them share a similar three-dimensional structure, referred to as the globin fold, characterized by a three-over-three alpha helical folding.…”
Section: Introductionmentioning
confidence: 99%
“…The recent and rapid accumulation of genomic information has resulted in a substantial increase in newly recognized globins. Bioinformatic genome surveys revealed that more than 50% of the bacterial, approximately 20% of the archaeal and almost 90% of the eukaryote genomes contain genes encoding globins [1,[5][6][7]. Despite their great variety in function and amino acid sequence, most of them share a similar three-dimensional structure, referred to as the globin fold, characterized by a three-over-three alpha helical folding.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive nomenclature, including prokaryotic and eukaryotic globins, assigns globins to three distinct families: (a) the myoglobin (Mb)-like family displaying the classical three-on-three (3/3) a-helical sandwich fold, and including flavohemoglobins (FHbs) and single-domain globins; (b) the sensor globin family; and (c) the truncated hemoglobin (TrHb) family that displays the two-on-two (2/2) a-helical sandwich fold [1]. Members of the TrHb family have been found in eubacteria, cyanobacteria, protozoa and plants, but not in animals [2].…”
Section: Introductionmentioning
confidence: 99%
“…For example, FMNH ⅐ formed via photoreduction reduces O 2 to ⅐ O 2 Ϫ , and ⅐ O 2 Ϫ can diminish or enhance the apparent O 2 rate constant by acting as a facile STAR reactant or STAR generator (9,11). STAR Toxicity Detoxification in Yeast-Evidence for damage to critical targets and scavenger protection within cells is essential for demonstrating a detoxification function (35,38,40). S. cerevisiae, an organism bearing mitochondria that produce sulfite (41, 42) but lack the sulfite-detoxifying sulfite oxidase (43) and that harbor the STAR-scavenging flavoHb (Yhb1p) .…”
Section: Fmn (mentioning
confidence: 99%